2020
DOI: 10.1186/s12911-020-01197-9
|View full text |Cite
|
Sign up to set email alerts
|

Professional training on shared decision making with older adults living with neurocognitive disorders: a mixed-methods implementation study

Abstract: Background Shared decision making with older adults living with neurocognitive disorders is challenging for primary healthcare professionals. We studied the implementation of a professional training program featuring an e-learning activity on shared decision making and five Decision Boxes on the care of people with neurocognitive disorders, and measured the program’s effects. Methods In this mixed-methods study, we recruited healthcare professionals in family medicine c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…In other countries, attempts have been made to use these scales for actual SDM training [ 33 – 35 ]. As older patients are increasing and the number of patients requiring interventions for mental and social problems is rapidly increasing, SDM training tools that can be commonly used by professionals in different job categories are required to support patient decision-based long-term care by interprofessional care teams including physicians.…”
Section: Discussionmentioning
confidence: 99%
“…In other countries, attempts have been made to use these scales for actual SDM training [ 33 – 35 ]. As older patients are increasing and the number of patients requiring interventions for mental and social problems is rapidly increasing, SDM training tools that can be commonly used by professionals in different job categories are required to support patient decision-based long-term care by interprofessional care teams including physicians.…”
Section: Discussionmentioning
confidence: 99%
“…This could be a key message in training programmes. An up-to-date systematic review of studies evaluating the effectiveness of recently developed shared decision-making training is warranted (91)(92)(93).…”
Section: Implications For Research and Practicementioning
confidence: 99%
“…Of all the studies, 69% (36/52) were published between 2019 and 2021 [ 9 , 32 - 68 ]. Furthermore, 58% (30/52) were located in Canada [ 7 , 8 , 10 - 12 , 23 - 25 , 28 , 31 , 35 , 38 - 41 , 44 - 51 , 53 , 54 , 56 , 60 , 63 , 65 , 67 ] and the rest in the United States (n=6), the United Kingdom (n=4), Australia (n=2) [ 30 , 34 ], Iran (n=2) [ 55 , 64 ], Argentina (n=1) [ 52 ], Indonesia (n=1) [ 32 ], Germany (n=1) [ 58 ], Sweden (n=1) [ 21 ], the Netherlands (n=1) [ 59 ], and Burkina Faso (n=1) [ 37 ]. In addition, two multicountry studies were reported: 1 from Brazil-China-France-Japan-Mali [ 68 ] and 1 from Canada-Vietnam [ 19 ] ( Table 1 ; Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%